Monitoring the "health" status of open source web-engineering projects. - Wahyudin, Dindin; Mustofa, Khabib; Schatten, Alexander; Biffl, Stefan; Tjoa, A. Min (Emerald Insight, 2007)
—In response to the increasing number of open source software (OSS) project initiatives and the increasing demand of OSS products as alternative solutions by industries, it is important for particular stakeholders such as the project host/supporter (e.g., Apache Foundation, Sourceforge), project leading teams, and prospective customers to determine whether a (new) project initiative is likely to sustain and worthwhile to support. From a software project management point of view, a typical web-based OSS project can be viewed as a web engineering process, since most OSS projects exploit the benefits of a web platform and enable the project community to collaborate using web-based project tools and repositories such as mailing lists, bug trackers, and versioning systems (CVS/SVN) to deliver web systems and applications. These repositories can provide rich collections of process data, and artifacts which can be analyzed to better understand the project status. This paper proposes a concept of ”health” indicators and an evaluation process that can help to get a status overview of OSS projects in a timely fashion and predict project survivability based on the project data available on web repositories. For initial empirical evaluation of the concept, we apply the indicators to well known web-based OSS projects (Apache Tomcat and Apache HTTP Server) and compare the results with challenged projects (Apache Xindice and Apache Slide). We discuss the results with OSS experts to investigate the external validity of the indicators.